Asparagus cochinchinensis: A review of its botany, traditional uses, phytochemistry, pharmacology, and applications - Wang, Meng; Wang, Shuang; Hu, Wenjing; Wang, Zhibin; Yang, Bingyou; Kuang, Haixue (Frontiers in Pharmacology, 2022)
Asparagus cochinchinensis (A. cochinchinensis) is a traditional herbal medicine that has been used to treat constipation, fever, pneumonia, stomachache, tracheitis, rhinitis, cataract, acne, urticaria. More than 90 compounds have been currently identified in A. cochinchinensis, including steroidal saponins, C21-steroides, lignans, polysaccharides, amino acids, and other chemical constituents. These bioactive ingredients make A. cochinchinensis remarkable for its pharmacological effects on anti-asthma, anti-inflammatory, anti-oxidation, anti-tumor, improving Alzheimer's disease, nerve protection, gut health-promoting and so on. Moreover, A. cochinchinensis also plays an important role in food, health products, cosmetics and other fields. Based on these studies, this review focused on the research publications of A. cochinchinensis and aimed to summarize the advances in the botany, traditional uses, phytochemistry, pharmacology, and applications which will provide reference for the further studies and applications of A. cochinchinensis.